2017
DOI: 10.1080/21623945.2017.1313374
|View full text |Cite
|
Sign up to set email alerts
|

Meeting report of the 2016 bone marrow adiposity meeting

Abstract: There is considerable interest in the physiology and pathology, as well as the cellular and molecular biology, of bone marrow adipose tissue (BMAT). Because bone marrow adiposity is linked not only to systemic energy metabolism, but also to both bone marrow and musculoskeletal disorders, this biologic compartment has become of major interest to investigators from diverse disciplines. Bone marrow adiposity represents a virtual multi-tissue endocrine organ, which encompasses cells from multiple developmental lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Under physiologic conditions, bone marrow adipocytes contribute to favor a balanced local fatty acid milieu in bone tissues that is determinant for healthy bone remodeling [ 68 ]. The results of this study shed light on the recent understanding of the role of the skeleton, more specifically of bone marrow adipocytes as important regulators of energy metabolism associated with osteogenesis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under physiologic conditions, bone marrow adipocytes contribute to favor a balanced local fatty acid milieu in bone tissues that is determinant for healthy bone remodeling [ 68 ]. The results of this study shed light on the recent understanding of the role of the skeleton, more specifically of bone marrow adipocytes as important regulators of energy metabolism associated with osteogenesis [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…81 Murine models have demonstrated that increasing MAT promotes the progression of osteolytic prostate cancer growth within bone. 82 Thus, it is commonly perceived that the presence of MAT results in bone loss with biomechanically compromised bones. However, little if any data is currently available demonstrating a causal relationship between MAT and low bone volume.…”
Section: Marrow Adipose Tissueautocrine Paracrine and Endocrine Intementioning
confidence: 99%
“…Obesity is correlated with increased MAT and studies in older men, postmenopausal women and children show that obesity increases the risk of fractures. 82,84,85 However, there are currently no data demonstrating a causative relationship between MAT and fractures. To better understand the relationship of diet, MAT and bone mineral density, we studied the effects of a high fat diet (HFD) on bone mass and MAT in B6 mice following long-(84 d in males) or short-term (14 d in males and females) HFD.…”
Section: Marrow Adipose Tissueautocrine Paracrine and Endocrine Intementioning
confidence: 99%
“…This group was funded by the French Research Agency with the goal of building a European network and applying to international funding calls. The need for the creation of a society was repeatedly posed during the 1st [BMA 2015, https://bma2015.sciencesconf.org: (3)] and 2nd BMA meetings [BMA 2016, https://adiposity.sciencesconf.org/; (4)] and in the last meeting of the BoneAHeaD group that took place in Boulogne-sur-Mer, France, in March 2017. At the BMA 2017, a preparatory meeting was organized on August 30th, 2017 (15:30–20:00) at EPFL in which members of the BoneAHead group invited speakers from the three BMA meetings (BMA 2015, BMA 2016, and BMA 2017) and other researchers who expressed an interest in the creation of an international society dedicated to BMA.…”
Section: Creation Of the International Bmasmentioning
confidence: 99%
“…In continuity with the first two meetings held in Lille, France [https://bma2015.sciencesconf.org; (3)], and in Rotterdam, the Netherlands [https://adiposity.sciencesconf.org/; (4)], the 3rd International Meeting on BMA was organized to provide physicians and scientists worldwide with different backgrounds -including bone biology, metabolism, oncology, endocrinology, hematology, and rheumatology- the opportunity to share novel results and exchange views on the emerging field of BMA (517). Reflecting the focus of the hosting laboratories, emphasis was placed on the bioengineering aspects and stem cell biology perspectives in BMA.…”
Section: Introductionmentioning
confidence: 99%